Compare Pre- and Post-Operative Refractive Errors in Patients Undergoing Cataract Surgery via Phacoemulsification (PHACO) Versus Manual Small Incision Cataract Surgery (SICS) - Dr Vandana Parasar; Dr Sudhanshu Shekhar; Dr Gyan Bhaskar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Purpose: To compare pre- and post-operative refractive errors in patients undergoing cataract surgery via phacoemulsification (PHACO) versus manual small incision cataract surgery (SICS). Methods: A prospective comparative study was conducted on 48 patients (24 in each group) with senile cataracts. Pre-operative and post-operative (at 6 weeks) refractive errors were assessed. Statistical analysis was performed using paired and unpaired t-tests. Results: The mean pre-operative spherical equivalent (SE) was comparable between groups (PHACO: -0.75 ± 1.25 D vs. SICS: -0.82 ± 1.30 D, p=0.85). Post-operatively, PHACO showed better refractive outcomes (SE: -0.25 ± 0.50 D) compared to SICS (SE: -0.65 ± 0.75 D) (p=0.02). Astigmatism was significantly lower in the PHACO group (0.50 ± 0.25 D vs. 1.25 ± 0.50 D, p<0.01). Conclusion: PHACO provides superior refractive outcomes with less post-operative astigmatism compared to manual SICS.